Ensino de solos em geografia: uma proposta de material de apoio para escolas estaduais de Francisco Beltrão – PR - Bedim, Milena Pellissari (2018)
This work aimed to highlight the importance of soil related subjects in school and its integration with other contents and variables of the geographic space, as well as to provide, from the perspective of Elementary and High School teachers in the municipality of Francisco Beltrão, a moment of reflection and systematization of pedagogical practices, linked to the teaching of soil science, in order to produce support material related to the local area and promote the quality of the education offered in public schools in Francisco Beltrão. Therefore, we used the case study methodology, which allowed the research carried out directly linked to the universe of those who work with the teaching of geography in Elementary and High School levels in Francisco Beltrão to be divided into two parts. The first consists of literature review; application of questionnaires to 24 (twenty four) teachers, out of the 40 (forty) who work in the state school system in Francisco Beltrão, and conducting semi-structured interviews with 21 (twenty-one) of these teachers. The second part, the research comprises the preparation of three workshop proposals for continuing teacher training on the teaching of soil science with the systematization of activities on the subject, from the indications given by teachers about the needs and gaps of support materials on this topic. As to the results, we found out that the subject of soils is covered by the teachers, and each professional has very rich experiences and perspectives regarding the teaching of this content. From the analyzed data, we verified that the teachers are excited about the methodological construction of their teaching practices, but they also show deficits in this sense. For this reason, the workshop proposals have as their main intention to help and support these teachers who work in the municipality in their demands and to encourage them to continue teaching soil in the their Geography classes.